Establishing the genome of Sukali ndizi - Pillay, M.; Hartman, J.; Dimkpa, C.O.; Makumbi, Dan (2003)
Cultivated bananas originated from interspecific hybridisation of two wild diploid (2n = 2x = 22) species, Musa acuminata and M. balbisiana that were the donors of the A and B genomes, respectively. Most cultivated bananas are triploids with 2n = 3x = 33 chromosomes. They vary in genome composition with the most common types being AAA (dessert), AAB (plantain) and ABB (cooking banana). Banana improvement programs make use of interspecific hybridisation for gene introgression. Consequently knowledge of the exact ploidy level and genome composition of a plant is important for breeding purposes. The ploidy level of a plant is generally determined in two ways: (1) by a physical count of its chromosomes, and (2) by flow cytometry. In this study, the ploidy level of the dessert banana cultivar, 'Sukali Ndizi', was determined by conventional chromosome analysis and flow cytometry. Our results showed that 'Sukali Ndizi' is a triploid. In the past, 'Sukali Ndizi' was considered to be a diploid with an AB genome composition. We also determined the genome composition of the cultivar using a set of RAPD (random amplified polymorphic DNA) markers and found that it has an AAB genome composition.